Transformative and Indigenous Frameworks in International Development - Mertens Donna M; Chilisa Bagele (International Journal for Transformative Research)
The international development community made a commitment to transformative goals related to social, economic, and environmental justice that requires them to leave no one behind. We argue that the use of transformative and indigenous frameworks for evaluation provide guidance towards achieving those goals. We provide a rationale for inclusion of these frameworks, along with an explanation of each framework and examples that illustrate their application. We conclude with hope for transformation on a global scale and reflections on our personal transformative experiences in conducting this work.